PENGARUH KEMAMPUAN INTELEKTUAL DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN YANG DIMODERASI OLEH ORGANIZATIONAL JUSTICE DAN SELF EFFICACY - Lukiyana Lukiyana; Arsinta Arsinta (Universitas Bunda Mulia, 2020)
This study aims to examine the effect of intellectual ability and career development on employee performance which is moderated by organizational justice and self efficacy at PT. Pelayaran Tempuran Emas, Tbk. Jakarta. The number of respondents studied by taking samples of 95 employees.Sampling method in this research using probability sampling method . In this research using PLS method ( Partial Least Square ) 3.0. The result of the data feasibility study proves that the result of the questionnaire is valid and reliable. This study led to the conclusion that intellectual ability significant positive effect on employee performance, career development significantly influence employee performance, organizational justice affects the performance of employees, self-efficacy affects employee performance, organizational justice is not able to moderate the relationship of intellectual ability to employee performance , organizational justice able to moderate career development relationship to employee performance, self efficacy not able to moderate the relationship of intellectual ability to employee performance , self efficacy is not able to moderate career development relationships to employee performance.Keywords: Employee Performance, Intellectual Ability, Career Development, Organizational Justice , Self Efficacy